Aplikasi perhitungan KPR berbasis android - Andri Saputra; Adi Santoso; Andhika Karta Negara; Ari Anggriawan (Teknomatika, 2014)
The prevalence of mortgage financing (mortgages) are caused due to the demand of society in the fulfillment house in installments. for people who need a home by way of mortgage banking role then was dominant. the basic principle is what will serve as a foothold or foundation to develop islamic banking products. mortgage calculations, problems that arise are usually not many people know the mortgage calculation process, the calculations were also still done manually in need of someone who can count them, knowing the formula calculation, require quite a long time, and have to know the interest rate on the gain from the bank, the problem of a single application for android-based mortgage calculations about the science, which is expected to help the community in doing the calculation process mortgages easy, and fast